Pembuatan NIB Dan Aplikasi Google Maps Dalam Pengembangan UMKM Desa Kebondalem Kabupaten Jombang - Putri Abidah Fauziyya; Farrah Ayu Rashida; Lukman Arif (Cv. Utility Project Solution, 2023)
Abstract MSMEs are considered a helping hand in restoring the nation's economy from the monetary crisis. However, the lack of access in marketing inside the market in Indonesia, makes MSMEs experience difficulties in increasing their income. This problem however, can be solve by digitizing MSMEs marketing efforts which are expected to be able to promote their products on the internet, one of which is by providing assistance through the means of registering MSMEs location on Google Maps. Apart from having Google Maps as a tool to assist digital marketing, there is something that is no less important, namely the Business Identification Number (NIB) which will facilitate business actors to save licensing data in one identity. Therefore, students carried out this community service as a form of support for MSMEs in Kebondalem Village, Bareng District. Jombang Regency in hopes that MSMEs are able to compete in the global market and helps business actors and to manage their business legality. This service starts from the preparation stage by visiting several MSMEs utilizing the door to door method. And continued with the implementation of registering NIB and Google Maps for each MSME.